The poetry of Bartłomiej Majzel: a psychoanalytic approach - Jurzysta, Marcin (Journal of Education Culture and Society, 2020)
Bartłomiej Majzel is one of the most interesting young polish authors. His first poetic book is robaczywość [worminess] published in 1997. As regards interpretation, many motifs which recur in the volume, suggest a psychoanalytic approach. This approach reveals a dark world of sub-consciousness and transcription of struggling against oneself, reporting the consequences of this tragic party called literature.